Culturally Responsive Teaching to Support Meaningful Learning in Mathematics Primary School: A Content Analysis in Student's Textbook - Murti, Rahayu Condro (Jurnal Prima Edukasia, 2023)
This study aims to measure and determine, through analysis, the textbooks used by elementary school students, especially in mathematics. The analysis seeks to examine how the aspects of culturally responsive teaching (CRT) in the textbook supports meaningful learning and supports the aspects of "Profil Pelajar Pancasila", specifically the global diversity in the "Kurikulum Merdeka". This research adopts a descriptive qualitative approach with a content analysis technique. The data source consists of mathematics teaching materials from the 4th-grade student textbooks, focusing on theme 5 "My Heroes," published by the Ministry of Education and Culture. Data collection was conducted through observation and documentation. The analysis includes the presentation of the material, consistency of the theme, consistency of learning outcomes, mathematics representation, and the three aspects of culturally responsive teaching. The results indicate that the contextual aspect of CRT is the most dominant in presenting meaningful learning. The CRT aspects in the textbooks, including explanations of concepts and examples of pictures presented, show that 8% are related to educational values, 11% to artifacts, and 81% to contextual meaning. The mathematics representation is appropriate with the theme and the learning outcomes. Therefore the teachers must provide additional learning on CRT aspects that are still lacking in textbooks.